Seatek Systems Pte Ltd - Tang, Hung Kei (2013)
When the phone rang, Mr. Y.K. Lang, general manager of Seatek Systems in Singapore, was considering his alternatives after a sobering meeting with the two PERT Associates consultants, who demonstrated why the M2K data logger would fail in the field. "Mr. Lang," said the contract manager of InduCorp icily, "if you can't offer a satisfactory solution to the field problems by September 1, 2001, consider the contract for the supply and installation of 500 M2K terminated... Oh, we also reserve the right to pursue compensation." Mr. Lang looked at the calendar and murmured to himself, "six weeks left!"